Review: BRUNCLÍK, Miloš; KUBÁT, Michal; VINCZE, Attila; KINDLOVÁ, Miluše; ANTOŠ, Marek; HORÁK, Filip; HÁJEK, Lukáš (2023). Power Beyond Constitutions: Presidential Constitutional Conventions in Central Europe. Cham: Palgrave Macmillan, 312 p., ISBN 978-3-031-34243-1. - Michael Drašar (Acta Politologica)
Review.